2015
DOI: 10.1038/ncomms9154
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-independent role for CRAF-driving tumour radioresistance via CHK2

Abstract: Although oncology therapy regimens commonly include radiation and genotoxic drugs, tumour cells typically develop resistance to these interventions. Here we report that treatment of tumours with ionizing radiation or genotoxic drugs drives p21-activated kinase 1 (PAK1)-mediated phosphorylation of CRAF on Serine 338 (pS338) triggering a kinase-independent mechanism of DNA repair and therapeutic resistance. CRAF pS338 recruits CHK2, a cell cycle checkpoint kinase involved in DNA repair, and promotes CHK2 phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 39 publications
0
41
1
Order By: Relevance
“…Further, PAK1 modulates the degree of DNA-damage response via directly phosphorylating microrchidia CW-type zinc finger 2 (MORC2-Ser739) and γH2AX (Li et al, 2012). In addition to radiation, PAK1 is stimulated by genotoxic therapeutic agents such as etoposide, and in-turn, PAK1 phosphorylates CRAF-Ser338 and causes radio-resistance (Advani et al, 2015). In general, PAK activation confers survival advantage to cancer cells against DNA-damaging agents, and hence, targeting PAKs has been thought as potential therapeutic approach to sensitize target cells in radiotherapy.…”
Section: Paks In Dna Damage Responsementioning
confidence: 99%
“…Further, PAK1 modulates the degree of DNA-damage response via directly phosphorylating microrchidia CW-type zinc finger 2 (MORC2-Ser739) and γH2AX (Li et al, 2012). In addition to radiation, PAK1 is stimulated by genotoxic therapeutic agents such as etoposide, and in-turn, PAK1 phosphorylates CRAF-Ser338 and causes radio-resistance (Advani et al, 2015). In general, PAK activation confers survival advantage to cancer cells against DNA-damaging agents, and hence, targeting PAKs has been thought as potential therapeutic approach to sensitize target cells in radiotherapy.…”
Section: Paks In Dna Damage Responsementioning
confidence: 99%
“…Mechanisms of resistance to therapies can be tumor cell intrinsic or mediated by the tumor microenvironment (3). We previously described intrinsic mechanisms of cancer cells' resistance to targeted therapy and radiotherapy (46). However, multiple factors can contribute to resistance to therapy and tumor progression, and one dominant player in solid cancers, and specifically in pancreatic cancer, is the presence of a rich protumoral microenvironment (710).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Advani et al . () showed how medication to CRAF_pS338 improves treatment; Duckworth et al . () concluded that overexpression of GAB2 promotes tumor growth; similarly, SF2 has been established as a critical pathway for human cancer cell survival, dissemination, and resistance to drug therapy (Wang et al ., ).…”
Section: Tcpa Protein Expression Datamentioning
confidence: 99%
“…The effects of these proteins on the cancers have been well studied in the literature. For example, Advani et al (2015) showed how medication to CRAF_pS338 improves treatment; Duckworth et al (2016) concluded that overexpression of GAB2 promotes tumor growth; similarly, SF2 has been established as a critical pathway for human cancer cell survival, dissemination, and resistance to drug therapy (Wang et al, 2014). PCADHERIN, FOXO3A_pS318S321, and DIRAS3 are the top 3 proteins recovered by all four chains.…”
Section: Protein Selectionmentioning
confidence: 99%